1994
DOI: 10.1073/pnas.91.13.5937
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tyrosine hydroxylase gene expression by a nonneuronal nonpituitary-mediated mechanism in immobilization stress.

Abstract: Stress stmulates the sympathoadrenal sys-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
98
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 36 publications
15
98
1
Order By: Relevance
“…Thus, elevation of PNMT is largely dependent on hormonal regulation at its glucocorticoid regulatory responseelement (Ross et al, 1990), and hypophysectomy prevents the induction of PNMT by stress, whereas TH, DBH, and NPY responses are affected only slightly (Nankova et al, 1994;Viskupic et al, 1994;Sabban et al, 1996). Transsynaptic nicotinic nerve stimulation is essential for the induction of adrenomedullary NPY , whereas immobilization stress was found to enable elevation of TH and c-Fos mRNAs by a nonneuronal, nonpituitarymediated pathway (Nankova et al, 1994;Sabban et al, 1995).In addition to the stress effects in the adrenal medulla, these genes are also elevated by stress in both the noradrenergic neurons of sympathetic ganglia and the locus ceruleus, the major noradrenergic cell bodies in the brainstem (Angulo et al, 1991;Mamalaki et a!., 1992;. However, there appear to be tissue-specific differences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, elevation of PNMT is largely dependent on hormonal regulation at its glucocorticoid regulatory responseelement (Ross et al, 1990), and hypophysectomy prevents the induction of PNMT by stress, whereas TH, DBH, and NPY responses are affected only slightly (Nankova et al, 1994;Viskupic et al, 1994;Sabban et al, 1996). Transsynaptic nicotinic nerve stimulation is essential for the induction of adrenomedullary NPY , whereas immobilization stress was found to enable elevation of TH and c-Fos mRNAs by a nonneuronal, nonpituitarymediated pathway (Nankova et al, 1994;Sabban et al, 1995).In addition to the stress effects in the adrenal medulla, these genes are also elevated by stress in both the noradrenergic neurons of sympathetic ganglia and the locus ceruleus, the major noradrenergic cell bodies in the brainstem (Angulo et al, 1991;Mamalaki et a!., 1992;. However, there appear to be tissue-specific differences.…”
mentioning
confidence: 99%
“…c-fos is a 62-kDa nuclear protooncogene that forms heterodimers with members of the Jun family; these complexes bind to AP-1 sites (core consensus of TGAG/CTCA) to regulate transcription (Angel and Karin, 1991). Immobilization and cold stress-elicited induction of cFos and increased binding to the AP-1-like site (TGA-TTCAG) in the TH promoter have been correlated with elevation in adrenal TH transcription (Miner et al, 1992;Nankova et a!., 1994). However, direct evidence regarding the role of c-Fos in mediating this induction or any stress-elicited changes in gene expression has been lacking.…”
mentioning
confidence: 99%
“…Some researchers (Nankova et al 1994;Kubovcakova et al 2004) have measured mRNA expression levels of catecholamine biosynthetic enzymes in the sympathetic ganglia after various kinds of stress and concluded that repeated and longer observation periods were required to detect an increase in the levels of transcripts in the sympathetic ganglia than in the adrenal glands. In those experiments, the shortest observation intervals were 2 h, which is much longer than those of the present study.…”
Section: Expression Levels Of Target Mrnas In the Anterocervical Gangliamentioning
confidence: 99%
“…On the other hand, measurement of sympathoadrenal activity based on expression levels of mRNAs for catecholamine biosynthetic enzymes has been performed in the field of molecular biology (Nankova et al 1994;Nankova et al 1996;Brooks et al 1997;Levenson and Moore 1998;Rusnák et al 1998;Bornstein et al 1999;Lai et al 2000;Sabban and Kvetnanský 2001;Gallara et al 2004;Kubovcakova et al 2004;Klimes et al 2005;Lai et al 2005;Herradón et al 2006). However, earlier animal studies on some stresses such as immobilization, cold exposure, forced exercise, and insulininduced hypoglycemia (Brooks et al 1997;Lai et al 2000;Sabban and Kvetnanský 2001;Gallara et al 2004;Klimes et al 2005;Lai et al 2005), did not cover all forms of stresses encountered in forensic practice.…”
Section: © 2008 Tohoku University Medical Pressmentioning
confidence: 99%
See 1 more Smart Citation